Aplikasi Sumbawa Excursion Berbasis Web Menggunakan Metode Waterfall - Eri Sasmita Susanto; Fahri Hamdani; Juniardi Akhir Putra; Ardi Susanto (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
Tourism activities are activities that are quite influential in boosting the economy in an area because they have abundant natural resource potential, interesting culture and unique and delicious culinary delights, which will help the community to improve the economy of each tourist area, by taking advantage of technological advances, namely internet, tourism objects in Sumbawa Regency can be easily promoted through a web-based application, in which there is various information related to tourism in Sumbawa Regency. Sumbawa Regency requires a Web Application so that it can help introduce tourism in the Sumbawa Regency to the wider community, especially people who are outside Sumbawa. Waterfall is the method used for the information system. Making this application will make it easier for the public to access information about tourism in Sumbawa Regency